A framework of key enabling drivers for innovation: Perceptions of community engagement scholarship of science fairs - Gibbs, M.D.; Poisat, P. (South African Journal of Higher Education, 2020)
ABSTRACT The focus of the article is to identify the main drivers for creating an innovative thinking environment, within the context of a community engagement project. Utilising reflexive practice with an analytical auto-ethnography approach, drivers of innovative thinking were identified from the field and experiences utilising existing theory in an educator, learner and community framework for driving innovation. The theoretical underpinnings of the three pillars used as the foundations for this framework were selected from literature in the people, place and process/purpose domains. Specifically, these were: Community Engagement Scholarship (people); creative Transdisciplinary Spaces (place) and Enabling Knowledge with common team vision (process/purpose). Certain pedagogical pathways were identified as critical enablers for driving innovation in this context: pedagogy, teaching strategies, mentoring, application-inquiry-based, safe spaces, critical thinking across disciplines, common vision, communication and collaboration. A framework of critical pedagogical pathways was proposed to drive creativity and innovation.